Medical workers of zhytomir oblast and assessment of the risks of their infection with SARS-COV-2 virus in the aspect of safety, occupational hygiene, and infectious control - Yavorovskyi, О.P.; Skaletskyi, Yu.M.; Brukhno, R.P.; Kharchuk, L.V.; Kyrychuk, I.M.; Borys, V.M.; Shuliarenko, V.P. (Environment & Health, 2021)
Objective: We assessed safety, occupational health and infectious control at the institutions of public health of Zhytomyr oblast of Ukraine to improve the management of the risks of the infection of medical personnel with the SARS-CoV-2 virus and to reduce the occupational morbidity and mortality of medical workers from COVID-19.Materials and methods: We used bibliographic, hygienic, questionnaire and mathematical methods in the study.The results of our own observations, questionnaires for a survey of medical workers, data of the Ministry of Health of Ukraine, the Center for Public Health of the Ministry of Health of Ukraine, the State Service of Ukraine for Labour, and thematic scientific sources of information were used as a material for the study.Results: The work of medical workers, involved in COVID-19 pandemic overcoming, is classified as dangerous (extreme). Besides SARS-CoV-2 virus, concomitant physical, chemical factors, and high physical and neuro-emotional stress affect the formation of working conditions in medical workers.Nurses (38.57%), junior nurses (26.10%), paramedics (5.37%), general practitioners of family medicine (4.85%), surgeons (4.16%), anesthesiologists (2.54%), infectious disease doctors (2.08%), radiologists (1.85%) are among medical workers who have been diagnosed with an acute occupational COVID-19 disease in Zhytomyr oblast of Ukraine.Conclusions: The main reasons of the high levels of occupational morbidity in medical workers of Zhytomyr oblast include personal carelessness of the victims; non-use of personal protection equipment if available; work in the focus of the disease; absence or poor-quality instruction on labour protection; not full provision with personnel in Zhytomyr oblast and medical workers with personal protection equipment in the medical institutions; shortage of epidemiologists, hygienists, and occupational pathologists.
Keywords: COVID-19; medical workers; working conditions; occupational morbidity; risk of infection